Contraintes Organisationnelles Et Resilience Chez Le Fonctionnaire Du Ministere Ivoirien De La Fonction Publique - Franck-Gautier, Gacha; Estelle, Assouman Ahou Mélissa (European Scientific Journal, ESJ, 2017)
Ivorian public Service is subject to criticism. To overcome this, reforms are undertaken to enhance its level of service. However, they apply at the expense of the human factor, which is essential to motivate. This communication builds on previous work, supplemented by semi-structured interviews with Ivorian officials. A content analysis of the discourse of actors was performed. It appears that the delay, corruption and absenteeism resulting from low wages as a source of motivation, as well as the lack of transparency on the decisions of the administrative organization and the small delegation of responsibilities. In a word, the administrative staff is always underway in the Public Service Ivorian. However, the human factor needs to trade, listening, evaluation of performance, information, motivation, mobilization.